EUL LIRIC LOTENIAN PĂTRUNS DE CHEMAREA STELELOR - CĂTANĂ, profesoară de limba și literatura română, Gimnaziul Peticeni, r-nul Călărași, Vera (BIBLIOPOLIS, 2020)
Emil Loteanu (1936-2003) was an actor, director, poet and writer from Moldova. The author investigates the personalized dimension of the Loteanu lyrical ego penetrated by „The Calling of Stars”. The theme proves its timeliness and importance by investing the lyrical ego as the mediator between the poet’s thoughts, feelings and emotions and the way they are received by the readers. Thus, any attitude of the lyrical ego corresponds to a certain extent with an image. Among the most frequently encountered are: the image of the seeking and the creative self.